The Artificial Anal Sphincter - John Christiansen (Canadian Journal of Gastroenterology)
The artificial anal sphincter as treatment for end stage anal incontinence was first described in 1987. Published series concern a total of 42 patients, with a success rate of approximately 80%. Infection has been the most serious complication, but a number of technical complications related to the device have also occurred and required revisional procedures in 40% to 60% of the patients. The artificial anal sphincter may be used for the same indications as dynamic graciloplasty except in patients with a previously irradiated or severely scarred perineum.